2012
DOI: 10.4236/ijcns.2012.57052
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Information Set Decoding Based on Genetic Algorithms

Abstract: In this paper, we describe a hard-decision decoding technique based on Genetic Algorithms (HDGA), which is applicable to the general case of error correcting codes where the only known structure is given by the generating matrix G. Then we present a new soft-decision decoding based on HDGA and the Chase algorithm (SDGA). The performance of some binary and non-binary Linear Block Codes are given for HDGA and SDGA over Gaussian and Rayleigh channels. The performances show that the HDGA decoder has the same perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 12 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…(7,4,3) code. The figures9, 10,11,12,13,14,15 and 16 represent a comparison of the performance of GOSMLD, HSDec and BM for some BCH codes. The obtained results prove that our technique reach the same performance of these decoders.…”
Section: Simulation Results and Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…(7,4,3) code. The figures9, 10,11,12,13,14,15 and 16 represent a comparison of the performance of GOSMLD, HSDec and BM for some BCH codes. The obtained results prove that our technique reach the same performance of these decoders.…”
Section: Simulation Results and Comparisonmentioning
confidence: 99%
“…In [14,15] several hard decoder based on genetic algorithms (GA) are developed, the first one is the HDGA (Hard decision Decoder based on Genetic Algorithms) [14], it used information sets to decode linear block codes. In [15], an efficient decoder called ARDecGA (Artificial reliabilities based decoding algorithm) is presented.…”
Section: Related Workmentioning
confidence: 99%
“…The methods for decoding algebraic block codes based on the joint application of the genetic algorithm, information sets and the Chase method are proposed in paper [20]. This research revealed that the efficiency of the presented hard decoding method is similar to that of the Berlecamp-Messi method.…”
Section: Literature Review and Problem Statementmentioning
confidence: 93%
“…Several hard decoder based on genetic algorithms (GA) were introduced. We begin by the HDGA (Hard decision Decoder based on Genetic Algorithms) [18], it exploits information sets to decode linear block codes; the second one is the Bit Flipping decoding algorithm (BF) [19,20] developed initially for LDPC codes and generalized after on linear block codes, it is based on the verification of many orthogonal equations. In [21], authors presented an efficient decoder called ARDecGA (Artificial Reliabilities based Decoding Genetic Algorithm); it is based on a generalized parity check matrix that computes a vector of artificial reliabilities of the binary received word and it uses a genetic algorithm to determine the maximum likelihood binary word to this vector.…”
Section: Relatedworkmentioning
confidence: 99%